المناخ المدرسي وعلاقته بالتكيف الاجتماعي لدى تلاميذ الصف الاول الابتدائي في محافظة اربيل/ المركز (Journal Of Educational and Psychological Researches, 2016)
The research aims at defining the level of the school environment and the social adjustment of the sample due to the sex and the relation among them. The two researchers have stated the school environment scale counting on the theoretical background and previous studies. As for the social adjustment scale, the researchers have used the scale of (Al-Kindy, 2001) and the school environment scale is implicated on (112) students. The schools and the students were elected in a random way. Whereas the social adjustment scale is implicated on (30) teachers in order to know their ratio of the student's adjustment. The results have appeared the satisfaction of the students on the private school environment within their school aspects (the director, the teacher and the methods of teaching), the increasing of their social adjustment level. The variations according to the sex, there were no variations within the aspects of the director and the methods of teaching. The results have showed the differentiations within the teachers for the benefits of the females. The results also showed the balance relationship among the variables. The researchers have stated several recommendations and proposela